Geophysical techniques for unconventional fracture characterization - Kristen Samy, R.R. (European Association of Geoscientists and Engineers, EAGE, 2021)
The thickness of the complex fracture beds in shale plays a major role in controlling the porosity and permeability in fractured shale reservoir. Shale has high number of fractures with high Poissonâs ratio, high Youngâs modulus, and high brittleness. These complex fractures affect the porosity and permeability in reservoir which impacts the production of oil and gas. Thus, the identification of fracture thickness is essential since it controls the porosity and permeability of shale reservoir. This study demonstrates on the identification of the thickness of fracture by geophysical method since it provides a solution. The thickness of fracture can be estimated using rock physics analysis followed by the selection of seismic attribute. Besides, RGB Blending and Unsupervised Vector Quantizer (UVQ) on fracture network can enhance the visibility of fracture since the minor fracture has low frequency due to its thickness. Lastly, generating wedge modelling is the final route to identify the thickness of fracture bed. We concluded, that, such kind of study for complex fracture help to improve the productivity from shales fracture reservoir and increase the production. Â© EAGE Asia Pacific Virtual Geoscience Week 2021. All rights reserved.